HBR's 10 must reads on emotional intelligence - Harvard business School (Boston, Massachusetts : Harvard Business Review Press, 2015)
This book is the definitive collection of idears and best practices for aspiring and experienced leaders alike.
Tặng
Keywords: Emotional intelligence; Work -- Psychological aspects